86.2k views
4 votes
1.075(5.25)x - 5.25(0.25)(x-3)

2 Answers

3 votes

Answer:

2.2575

Explanation:

User Suzon
by
5.1k points
4 votes

For this case we must simplify the following expression:


1,075 (5.25) x-5.25 (0.25) (x-3) =

So, solving the first parentheses we have:


5.64375x-1.3125 (x-3) =

We have to:


- * + = -\\- * - = +\\5.64375x-1.3125x + 1.3125 (3) =\\5.64375x-1.3125x + 3.9375 =

We add similar terms taking into account that different signs are subtracted and the sign of the major is placed:


4.33125x + 3.9375

Finally, the simplified expression is:
4.33125x + 3.9375

ANswer:


4.33125x + 3.9375

User Wuliwong
by
5.4k points